The role of the school principal in enhancing teacher professionalism at Sekolah Indonesia Kuala Lumpur (SIKL) - Amrillah, Rizki (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The main purpose of this study is to investigate the roles of school principal toward enhancing teacher professionalism at Sekolah Indonesia Kuala Lumpur (SIKL). It is also aimed at affirming the most influential roles implemented in school by school principal as perceived by teachers. Furthermore, this study is also designed to determine (if any) there is relationship between the roles of school principal and teacher professionalism. This study used quantitative method to obtain its objectives. This study used purposive sampling procedure to select the sample of population was applied to select 40 teachers in school. The results showed that the teachers perceived the role of school principal as curriculum leader dominating, it followed by the school principal as leader in school and as manager in school. The relationship between each the roles of school principal and teacher professionalism was statistically significant. Based on the findings of this study it was recommended that similar studies should be conducted on a nationwide basis whereby the findings, suggestions and recommendations would be the source of guidelines in developing teachers for training programs, they could be applied to the current curriculum system of schools and become key performance indicator to acknowledge best school curriculum, achievement and best principal award. For contemporary and prospective school as well as superb school principal.